A review on the effect of RAP recycling on bituminous mixtures properties and the viability of multi-recycling. (30th June 2019) - Antunes, V.; Freire, A.C.; Neves, J.
Graphical abstract: Highlights: RAP recycling in bituminous mixtures presents economic, social and environmental benefits. RAP mixtures performance depends on origin, additives and incorporating techniques. RAP mixtures can exhibit higher stiffness and rutting resistance, but lower fatigue resistance. High RAP incorporation rates are possible ensuring adequate long-term performance. Further research is needed in terms of RAP multi-recycling capacity. Abstract: Every year road agencies allocated large budgets to road construction and there is a need to implement more economically and environmentally sustainable practices. The maintenance operations produce a considerable amount of Reclaimed Asphalt Pavement (RAP) and its incorporation in new mixtures has economic and environmental benefits. The main objectives of this paper are to present an extensive review of the existing knowledge and experience on RAP incorporation in new bituminous mixtures – RAP mixtures – and also to evaluate its multi-recycling potential. The mechanical performance of RAP mixtures is affected by intrinsic and external variables. Intrinsic variables as gradation, bitumen content and volumetric properties can lead to different behaviours. Additionally, the RAP incorporation methods, as well as the addition of a rejuvenator and/or a softer bitumen to obtain the intended viscosity in the binder blend can also affect the final behaviour of the recycled mixture.